Effect of Silane Concentration on the Physical and Mechanical Properties of Bacterial Cellulose Silylated Aerogels - Nazarudin Zakaria, Mohd; Hishammuddin, Nuraqilah; Nazifa Fairos, Norsyasha; Nurhakim Syafiq Mohd Nasir, Mohamad; Abdul Rahman, Sukirah (International Journal of Engineering and Technology, 2018)
Bacterial cellulose (BC) produced by Acetobacter xylinum shows unique physicochemical properties. In this research, silane has been used as coupling agent to coat bacterial cellulose to change the properties of BC from hydrophilic to hydrophobic. Different silane concentrations (0%, 5%, 10% and 15%) were applied to determine the physical and mechanical properties of BC-silylated aerogels. Supercritical fluid extraction (SFE) process was used to get the 3D shape of BC aerogels since the separation of components using carbon dioxide as supercritical fluids occur faster than common extraction. BC membrane was characterized by FESEM and it is shown that porosity of BC membrane was affected with silane concentration. For physical testing, silane concentration has no effect on porosity of the BC aerogels while water absorption and thickness swelling showed that BC membrane coated with 15% silane concentration can be used for water or gas filtration.